Bicuspid Valve-Related Aortic Disease: Flow Assessment with Conventional Phase-Contrast MRI - Burris, Nicholas S. (Acad Radiol, 2015)
RATIONALE AND OBJECTIVES: Abnormal blood flow with bicuspid aortic valve (BAV) has been characterized with four-dimensional flow magnetic resonance imaging (MRI), but this approach is time consuming and requires technical expertise. We assess the relationship between different leaflets fusion patterns with BAV, eccentric systolic flow, and dilation patterns of the ascending aorta using two-dimensional (2D) phase-contrast (PC) MRI. MATERIALS AND METHODS: Fifty-nine patients with BAV who underwent cardiac MRI were identified; 47 had right–left (RL) aortic leaflet fusion and 12 had right-noncoronary (RN) fusion. Flow displacement was calculated, and patients with abnormal displacement (>0.1) were classified as either rightward or leftward. Patterns of aortopathy were determined (0–3), and correlation between leaflet fusion, flow direction, aortopathy type, and other clinical parameters was performed with Pearson correlation, the Fisher exact test and chi-square analysis. RESULTS: Normal systolic flow was seen in 24% of cases and was significantly correlated with normal aortas (P = .011). Abnormal flow displacement with RL fusion was strongly associated with rightward deviation (36 of 37 cases), whereas RN fusion skewed leftward (seven of eight cases; P < .01). In patients with aortopathy, RL fusion was strongly associated with type 2 aortopathy and RN with type 3 aortopathy (P < .01). CONCLUSIONS: Conventional PC MRI can identify abnormal systolic flow and differences in jet orientation with BAV. RL leaflet fusion is associated with rightward flow deviation and type 2 aortopathy, whereas RN fusion is linked to leftward deviation and type 3 aortopathy. The presence and direction of eccentric flow jets may help risk stratify these patients for valve-related aortic disease.